Analysis of dibutyl phthalate and oleamide in stingless bee honey harvested from plastic cups - Yee, Ping Koo; Noorfatimah Yahaya,; Wan Adnan Wan Omar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Increasing demands for stingless bee honey in Malaysia have prompted alternative method using plastic cups as artificial honey pots within beehives to enhance yield. However, honey’s acidity may lead to migration of plastic additives, affecting body’s physiological responses on prolonged consumption. This study was performed to determine the presence of dibutyl phthalate (DBP) and oleamide in stingless bee honey collected from plastic cups. A method for simultaneous extraction and detection of both analytes by solvent terminated dispersive liquid-liquid microextraction (ST-DLLME) coupled with high performance liquid chromatography (HPLC) was developed. Good linearity was observed with coefficient of determination R2 ≥ 0.97 in the concentration range of 0.5-50 and 10-250 μg/g for DBP and oleamide, respectively. The limit of detection for DBP was 0.15 μg/g; while oleamide was 4 μg/g. The limit of quantitation for DBP and oleamide was 0.5 and 11 μg/g, respectively. DBP and oleamide were not detected in all the honey samples collected.